INFLUENTIAL FACTORS OF PURCHASE INTENTION ON BRAND X LOCAL BEAUTY PRODUCTS - Wijaya, Silvia; Ekawati , Sanny (International Journal of Application on Economics and Business, 2024)
The interest in beauty products has recently increased. This research aims to evaluate empirically regarding the impact of E-WOM, brand awareness, and brand image in creating buying interest when purchasing local beauty products in Jakarta. The sample size of this research was 156 respondents with purposive sampling technique. Data collected in this study used questionnaires distributed online through social media to those using brand X local beauty products in Jakarta. Data which have been collected was examined using PLS-SEM with the assistance of version 3 software of SmartPLS. The results showed that E-WOM has a positive and significant impact regarding brand awareness and brand image, while E-WOM and brand awareness do not have a significant influence on purchase intention. In addition, brand image has a positive and significant influence on purchase intention. The benefit of this research for local beauty companies is to manage their marketing communications well so as to engage customer reviews and pay close attention to the brand image that is formed so as to increase customer desire to buy and recommend products to others.